Relationships Between Annual and Perennial Seagrass (Ruppia sinensis) Populations and Their Sediment Geochemical Characteristics in the Yellow River Delta - Gu, Ruiting; Song, Xiaoyue; Zhou, Yi; Xu, Shaochun; Xu, Shuai; Yue, Shidong; Zhang, Yu; Zhang, Xiaomei (Frontiers in Plant Science, 2021)
Annual and perennial population traits are common in the same submerged aquatic angiosperm species, yet relationships between the population traits and sediment characteristics are poorly understood. This study surveyed two Ruppia sinensis populations in the Yellow River Delta with different population traits. The biomass and their seasonal seed bank size were used to evaluate their population status and potential recruitment capacity. Nine parameters were measured to assess sediment nutrient composition and variability. The results showed relatively higher biomass and more intensive seed bank sizes in annual R. sinensis population than perennial population. Different population traits of R. sinensis were resulted from the appearance of overlying water rather than the sediment nutrition, which showed different resilience capacities after exposure to the desiccation of the habitat. The ‘OM’ is more sensitive than ‘TOC’ when describing the carbon cycling in R. sinensis sediment. Our result brought a further knowledge of R. sinensis population, and could serve as a reference for Ruppia population conservation and management.